Lanzhou Lily polysaccharide fragment protects human umbilical vein endothelial cells from radiation-induced DNA double-strand breaks. (11th November 2022) - Kang, S; Guo, Z; Zhao, F; Song, L; Lu, L; Wang, C; Liu, Z; Zhao, J
Background: Radiotherapy is widely used in the treatment of tumors. However, while killing tumor cells, radiation may also cause damage to the surrounding normal tissues. Therefore, it is very important to find safe and effective radiation protection agents. Purpose: To investgate the radiation protection effect of Lanzhou Lily polysaccharide fragments (LLP). Methods: The crude polysaccharides of Lanzhou Lily were extracted from the dried bulb powder of Lilium lilium by ultrasonic-assisted hot water method, and then five different fragments were separated from the polysaccharides by DEAE-52-cellulose column. The 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyl-2H-tetrazolium bromide assay, neutral comet and immunofluorescent staining were used to investigate the effect of LPe fragment on Human Umbilical Vein Endothelial Cells (HUVEC) survival and the possible radioprotective mechanism. Results: The LPe fragment (composing of mannose and glucose, with a ratio of 5.5:2.9, and the average molecular weight is 8629.8 Da), significantly promoted the proliferation of HUVECs and protected cells from X-ray-induced double-strand breaks (DSBs) in DNA, in which pretreatment with the LPe fragment at 100 μg/mL showed the most pronounced protection. In addition, the occurrence of X-ray-induced γH2AX foci was significantly reduced by treatment with the LPe fragment at 50, 100, and 200 μg/mL. Furthermore, caffeine or wortmannin in combination with the LPe fragment at 25 μg/mL significantly reduced the number of X-ray-induced γH2AX foci, indicating phosphoinositide-3 kinases (PI3K) is involved in H2AX phosphorylation in HUVECs. Conclusion: These results indicate the LPe fragment has a protective effect against radiation-induced DSBs and may be used as a natural antioxidant agent.